Evaluation of water lettuce, giant salvinia and water hyacinth systems in phytoremediation of domestic wastewater - Mustafa H.M.; Hayder G. (IWA Publishing, 2023)
The objective of this research was to ascertain the best conditions for efficient applications of water lettuce, giant salvinia and water hyacinth in improving the quality of low strength domestic wastewater. Water quality assessment of the wastewater samples before (influent) and after treatment (effluent) with effect to retention times (6, 12 and 24 h) was analysed. The outcome of the study at 6 h retention showed that water lettuce (6.8-7.0 pH, 50.5% colour, 46.7% biochemical oxygen demand (BOD) and 37.8% chemical oxygen demand (COD)), giant salvinia (6.9-7.1 pH, 40.5% colour, 60% BOD and 43.2% COD) and water hyacinth (6.7-6.9 pH, 45.5% colour, 53% BOD and 35.1% COD) reduction values were achieved. At 12 h retention, water lettuce (6.6-7.0 pH, 57.2% colour, 77.1% BOD and 74.6% COD), giant salvinia (6.4-6.8 pH, 81.1% colour, 66.7% BOD and 72.2% COD) and water hyacinth (6.4-6.7 pH, 61.9% colour, 70% BOD and 61.1% COD) reduction values were achieved. Similarly, for 24 h retention, water lettuce (6.6-7.0 pH, 76.7% colour, 53.2% BOD and 70.3% COD), giant salvinia (6.6-7.0 pH, 91.4% colour, 74.7% BOD and 81.0% COD) and water hyacinth (6.4-6.9 pH, 74% colour, 58% BOD and 67.2% COD) reduction values were achieved. These findings indicated that the retention times of 12 and 24 h provided suitable conditions to break down the organic contaminants present in the shallow ponds. 2021 The Authors.